Surface ultrastructure of the puparia of the blow fly, Lucilia cuprina (Diptera: Calliphoridae), and flesh fly, Liosarcophaga dux (Diptera: Sarcophagidae) - K. L. Sukontason (2018)
Surface ultrastructure of the puparia of the blow fly, Lucilia cuprina, and flesh fly, Liosarcophaga dux, are presented utilizing scanning electron microscopy (SEM). Emphasis was focused on characteristic features of the puparia that could be used for differentiation from other forensically important fly species. The puparium of L. cuprina typically measures 6.2±0.2 mm in length and 2.3±0.1 mm in width. Each anterior spiracle contains a single row of 5-7 papillae. The intersegmental spines between the prothorax and mesothorax are triangular with constricted tips. A clustered bubble membrane, comprising about 30 mammillate structures, is positioned dorsolaterally on each side of the first abdominal segment in young puparia but is replaced by short, tubular respiratory horns in aged puparia. The posterior end of the puparium is broadly truncate and bears a pair of medially positioned posterior spiracles that each contains three straight spiracular slits. The puparium of L. dux is larger in comparison to L. cuprina and typically measures 9.9±0.3 mm in length and 3.8±0.2 mm in width. An anterior spiracle of this species contains 14-17 papillae. The intersegmental spines between the prothorax and mesothorax are broad and triangular. A convoluted structure of unknown function was observed at the dorsolateral edge of segments 5-11. In L. dux, the caudal segment of the puparium is slightly tapered and abruptly truncated and contains a pair of posterior spiracles that are located within a deep concavity in the terminal end. Each posterior spiracular disc appears D-shaped, with a pronounced medial projection and three vertically oriented long, narrow spiracular slits. The anatomical features presented herein may be useful for identification of fly puparia of these two species in future forensic entomological investigations. © Springer-Verlag 2006.